Ecosystem restoration and belowground multifunctionality: a network view - Tian, Dashuan; Xiang, Yangzhou; Seabloom, Eric; Chen, Han; Wang, Jinsong; Yu, Gui-Rui; Deng, Ye; Li, Zhaolei; Niu, Shuli (Dryad, 2022)
Ecological restoration is essential to reverse land degradation worldwide.
Most studies have assessed the restoration of ecosystem functions
individually, as opposed to a holistic view. Here we developed a
network-based ecosystem multifunctionality (EMF) framework to identify key
functions in evaluating EMF restoration. Through synthesizing 293
restoration studies (2900 observations) following cropland abandonment, we
found that individual soil functions played different roles in determining
the restoration of belowground EMF. Soil carbon, total nitrogen and
phosphatase were key functions to predict the recovery of belowground EMF.
On average, abandoned cropland recovered about 19% of EMF during 18 years.
The restoration of EMF became larger with longer recovery time and higher
humidity index, but lower with increasing soil depth and initial soil
carbon. Overall, this study presents a network-based EMF framework,
effectively helping to evaluate the success of ecosystem restoration and
identify the key functions.
We searched literature on the topic of 'Grain for Green program'
in China and belowground functions during 1900-2019, by means of Web of
Science, Google Scholar and China Knowledge Resource Integrated Database.
This program aims to reduce water and soil erosion, enhance soil
fertility, and recover degraded ecosystems. Restoration techniques include
active and natural ecosystem restoration. We restricted our analyses to
changes in soil C, N and P cycling processes, when croplands were restored
to semi-natural ecosystems (i.e., forest, shrubland and grassland). The
papers collected were further screened on the basis of the following
criteria. First, both agricultural and restored sites shared similar
climate and soil conditions. Second, studies were performed with paired
sites, using chronosequence or retrospective design. Third, soil depth and
restoration time were clearly described. Finally, belowground functions
were explicitly shown by their mean values and sample sizes. Based on
these criteria, we identified 293 studies from 272 papers that were
suitable for our analysis. Table-form data were directly gathered from
original papers, and figure-form data were digitized and extracted by the
Engauge Digitizer (Free Software Foundation, Inc., Boston, MA). Overall,
our dataset (2900 observations) spanned a mean annual precipitation range
of 116 to 1980 mm and annual temperature range of -0.7 to 20.5 °C.
Restored ecosystems included forests, shrublands and grasslands, with the
restoration time from 1 to 100 years. Belowground processes represented
multiple functions of storing nutrients (soil organic carbon-SOC, total
N-TN, total P-TP), transforming nutrients (microbial biomass C-MBC,
microbial biomass N-MBN, microbial biomass P-MBP, invertase, catalase,
urease, phosphatase) and supplying nutrients (available N-AN, available
P-AP).
(1) What else would someone need to know to use this dataset? No
(2) Are there any missing values?  No
Keywords: cropland conversion; ecosystem restoration; functional network; meta-analysis; multifunctionality; FOS: Agriculture, forestry, and fisheries